The Role of Independent Commissioners in Moderating the Effect of Capital Intensity, Inventory Intensity, and Profitability on Tax Aggressiveness - Pratama, Indriyani; Suryarini, Trisni (Accounting Analysis Journal, 2020)
The study aimed to analyze the effect of capital intensity, inventory intensity, and profitability on tax aggressiveness with a board of independent commissioners as a moderating variable. Property and real estate companies listed on the Indonesia Stock Exchange in 2014-2018 were the population in this study. Sampling in this study used a purposive sampling technique. The sample selection in this study used a purposive sampling technique so that there were 24 companies with 120 analysis units. The method of analysis used in this study was the panel data regression method using the Eviews 9 application program. The results showed that capital intensity and inventory intensity partially do not have a significant effect on tax aggressiveness, while profitability partially has a significant positive effect on tax aggressiveness. The board of Independent commissioners is not able to moderate the effect of capital intensity, inventory intensity, and profitability on tax aggressiveness. The conclusion of this study is only profitability which has a significant effect on corporate tax aggressiveness, so it is proven that the more profit the company receives will trigger the company to take tax aggressiveness. Keywords: Tax Aggressiveness; Capital Intensity; Inventory Intensity; Profitability; Independent Board of Commissioners